THE IMPACT OF THE AZERBAIJANI LANGUAGE VOCALISM ON BAKU RESIDENTS RUSSIAN PRONUNCIATION: THE BILINGUAL ASPECT - Sanay H. Huseynli (Alfred Nobel University Journal of Philology, 2022)
The Russian speech of the Baku people has its own long-standing traditions and, at the same time, its own special dynamics of development. Modern social conditions expand the Russian-Azerbaijani bilingualism possibilities, which makes the study of this sociolinguistic phenomenon relevant. The aim of the article is to study the specifics of Azerbaijani vocalism influence on the Russian speaking Baku residents; to identify the characteristic speech features of Azerbaijani and Russian speakers in the context of bilingualism issues. The features of oral speech depend on many objective and subjective factors, the consideration of which requires the use of direct observation method, experimental phonetics (acoustic instrumental method) and sociophonetics method (survey). In the process of research we used monologues and dialogues of native speakers in a student audience, on social networking sites, on the meetings at various cultural and other events, in everyday life and family. Speeches were recorded on paper and technical media for further consideration. We studied the general scientific and theoretical prerequisites of the problem, the features of the Azerbaijani and Russian languages phonetic system, including vowels. Participants in oral speech are grouped according to a number of parameters, namely: those who received education in Russian or in Azerbaijani; age groups (up to 30 years old, from 30 to 50 years old, over 50 years old); living mainly in the environment of the Russian-speaking population, living outside it. The vowels of the Azerbaijani language are grouped depending on the place of their formation and the nature of pronunciation, each group is considered separately in the context of Baku citizens influence on the Russian pronunciation. We considered the influence of the Azerbaijani language vowels, which are unusual for the Russian language, on the Russian speech of Baku people (ə, ö, ü). It is noted that the influence of these sounds is reflected in words borrowed from other languages and used in each of the studied languages. The fact of using vowel sounds that are absent in Russian is analyzed based on the law of harmony inherent in all Turkic languages. We revealed the fact of sounds intonational distortion in Russian. The influence is especially noticeable in the patterns of “macaronic” speech. The features of the pronunciation of some vowels in the Russian speech of Baku residents should be characterized taking into account the sociolinguistic features of the speakers. We took into account age, position in the social structure, education (received in Russian or Azerbaijani), professional affiliation (for example, the speaker can be a Russian language teacher or a Russian-speaking journalist, TV presenter, etc., that is, a good speaker of Russian language due to their training). The affiliation of the speaker to one or another dialect or patois of the Azerbaijani language is also important, moreover, if he/she received an education in the Azerbaijani language. So, the impact of the Azerbaijani language vocalism on Baku residents Russian pronunciation in the bilingual space is reflected in the following factors: 1. There are features of Azerbaijani vowels intensive use, which are associated with sound position, its features of application within the framework of assimilation or harmony laws. For example, a, o, u, ı, i are more similar than other vowels. Or, for instance, e, ə, ö, ü at the place of their formation, are able to influence other vowels, and are intensively used in the second and subsequent syllables of the word. Also in combination with each other. All this is reflected in the nature of the Russian speech of Baku city inhabitants. 2. The influence of the vowels ə, ö, ü, which are not specific for Russian phonemes, comes through the pronunciation of Azerbaijani words included in the vocabulary of Baku residents (names, household items, geographical names, etc.) in the “Azerbaijani” way, that is, with the preservation phonetic features of these words. 3. Vowel sounds are added based on the law of harmony, which is specific for all Turkic languages (and not only!). 4. There are intonation changes associated with the lengthening of a vowel sound in a word, or the use of expressions like a-a-a, uh-uh in sentences to show an emotional attitude to what was said. 5. The nature of the relationship between vowels in the Azerbaijani language can be weak, intense or contradictory, that is, generally impossible. It is these features that affect pronunciation, intonation, the choice of words and their use in the text of speech. It is rather difficult to reflect all the features of the use of Azerbaijani vowels within the framework of the article; however, the main points are reflected. The softness and hardness of Russian consonants, which directly affect pronunciation, is important. There is a lack of certain reductions of vowels, and there are manifestations of rhythm disturbances.